Planting Date and Maturity Group Interaction for Soybean Productivity and Seed Quality in East Central Kansas - L. P. Pott; L. H. Moro Rosso; W. D. Carciochi; J. Kimball; E. A. Adee; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2019)
Soybean seed quality is an important component for soybean meal. Different factors affect seed quality, such as genetics, environment, and management (G × E × M). The objectives of this study were to 1) evaluate the effect of planting date and maturity group in soybean seed quality (protein and oil concentrations) and 2) investigate the relationship between soybean seed quality and productivity (seed weight and yield). Three field experiments were conducted during the 2018 growing season evaluating the combination of two factors, planting date and maturity group, with three levels of each one (early, medium, and late). Field measurements included: seed yield, seed weight, and seed quality, mainly represented by determination of seed protein and oil concentrations. The main outcomes of this study were: 1) early planting date resulted in the highest protein and oil concentrations, while late planting date presented the lowest concentrations for those seed quality components; and 2) protein concentration was negatively correlated with seed yield (r = -0.66).
Keywords: soil health; cover crops; enzymes; microbial activity